(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
In a welfare state the executive branch of governmentexercise a dominating authority over the governmental functions. The everexpanding span of executive power drowse in the enlarged categories of quasilegislative and quasi-judicial functions. The adoption of development, makingof welfare plans and commitment to the attainment of objectives ofsocio-economic revolution, policy and legislation for securing the applicationof the principles of public and legislation for securing the application of theprinciples of public welfare policy for people, like directive Principles ofState Policy under part IV of Indian Constitution, have expanded the arena ofgovernmental responsibilities and powers resulting into expanded functionalscope of executive branch.